CONTEMPORARIES ON HABSBURG POLITICAL ASPIRATIONS AND PLANS FOR MILITARY OCCUPATION OF BOSNIA AND HERZEGOVINA 1787–1875. - Teinović, Bratislav (Politeia, 2024)
The paper presents an overview of the most important aspirations and plans of the Habsburg Monarchy for the occupation of the Bosnia and Herzegovina, from the historic 1787 agreement between the Russian Empress Catherine II and the Habsburg Emperor Joseph II on the division of geopolitical spheres of interest in the Balkans to the start of the uprising of Serbs in Bosnia and Herzegovina in the summer of 1875. Based on the accounts of first-hand witnesses of these events (Boué, Spencer, Arbuthnot, Stillman) and  research of relevant Serbian (Popović, Stojanović, Ekmečić, Petrović, Berić, Šljivo, Tatić) and international (Spaits, Marriott, Sumner, Harris, Rupp, Taylor, Burns) historians, the paper introduces only those political aspirations and plans that openly indicate unambiguous military occupational tendencies of the Vienna government towards the most far west Ottoman province in the Balkans and in Europe.
Keywords: Habsburg Monarchy; Ottoman Empire; Bosnia and Herzegovina; Vienna government; Аustria/Austro–Hungary; politics; uprisings